Distinctive autophagy/mitophagy biomarker profiles in frontotemporal lobar degeneration and Alzheimer's disease - Veverová, Kateřina; Katonová, Alžběta; Horáková, Hana; Laczó, Jan; Angelucci, Francesco; Hort, Jakub; Lautrup, Sofie; Fang, Evandro Fei; Vyhnálek, Martin (Acta neuropathologica communications, 2025)
Maintaining cellular homeostasis by removing damaged and senescent mitochondria, a process termed mitophagy, is crucial in preventing Alzheimer's disease (AD) and represents a promising therapeutic target. Our previous research revealed altered mitophagy biomarkers, such as increased CSF and serum PINK1 and serum BNIP3L and decreased serum TFEB levels, indicating impaired autophagy-lysosomal degradation in the AD continuum. However, the role of autophagy/mitophagy in frontotemporal lobar degeneration (FTLD) remains unclear. This study investigated the biomarkers of autophagy/mitophagy and lysosomal biogenesis (PINK1, ULK1, BNIP3L, and TFEB) in biofluids (CSF and serum) from 308 biomarker-defined individuals across the FTLD continuum (FTLD-dementia, n = 29; FTLD-MCI, n = 33) and compared them with those across the AD continuum (MCI-AD, n = 100; AD-dementia, n = 100) and cognitively unimpaired (CU) controls (n = 46) recruited from Czech Brain Aging Study. Additionally, we compared the mitophagy biomarkers across different FTLD clinical subtypes (frontal, semantic and nonfluent variant) with CU, and explored the association between mitophagy biomarkers and clinical phenotypes of FTLD (biomarkers of tau, biomarkers of neurodegeneration, cognition and ATN profile).Our findings indicated a significantly lower CSF PINK1 and ULK1 levels in FTLD compared to AD, with FTLD dementia showing particularly low CSF PINK1 levels compared to AD-dementia. Conversely, CSF ULK1 levels were higher in FTLD-MCI compared to AD-dementia. Serum analyses revealed lower PINK1 and higher TFEB levels in FTLD dementia compared to AD dementia. This study provides compelling evidence of distinct alterations in autophagy/mitophagy biomarkers between FTLD and AD, indicating that these neurodegenerative diseases may affect the cellular waste disposal system through different pathways. This is the first study to explore mitophagy biomarkers in human CSF and serum in FTLD, opening avenues for further research and potential clinical applications.
Keywords: autofagie; Frontotemporal lobar degeneration; Male; intracelulární signální peptidy a proteiny; biologické markery; Biomarkers; Alzheimerova nemoc; Alzheimer Disease; frontotemporální lobární degenerace; proteinkinasy; Aged; Intracellular Signaling Peptides and Proteins; mužské pohlaví; senioři; Neurocognitive impairment; senioři nad 80 let; Protein Kinases; Autophagy; lidé; Autophagy-Related Protein-1 Homolog; ženské pohlaví; mitofagie; Humans; Frontotemporal Lobar Degeneration; PINK1, TDP-43, TFEB; Aged, 80 and over; Mitophagy; homolog Atg1; Female; lidé středního věku; MAPT; Middle Aged